Lessons learnt: montados in Portugal - Faias, Sónia Pacheco (2017)
The AGFORWARD research project (January 2014 - December 2017), funded by the European Commission, is promoting agroforestry practices in Europe that will advance sustainable rural development. The project has four objectives: 1. to understand the context and extent of agroforestry in Europe, 2. to identify, develop and field-test innovations (through participatory research) to improve the benefits and viability of agroforestry systems in Europe, 3. to evaluate innovative agroforestry designs and practices at a field-, farm- and landscape scale, 4. to promote the wider adoption of appropriate agroforestry systems in Europe through policy development and dissemination. This report contributes to the second objective and Deliverable 2.5 which describes the lessons learnt from innovations within agroforestry systems of high natural and cultural value. Within the project, there were ten stakeholder groups focused on such systems (e.g. dehesas, montados, other wood pastures, and bocage). This report focuses on a trial established to understand the effect of understory management alternatives on the tree and cork growth, in pure cork oak woodlands, also commonly known in Portugal as ”Montado”